STRATEGIC APPROACH IN THE SYSTEM OF ANTI-CRISIS FINANCIAL MANAGEMENT IN HEALTH CARE INSTITUTIONS - MOROZ, OLENA; MOROZ, IEVHENIIA; KATILOVA, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The issues of improving the system of anti-crisis financial management in health care institutions of Ukraine are considered in the article taking onto account the strategic approach. The strategic approach gives a competitive advantage and the ability to develop measures to achieve goals in a competitive dynamic space. On the example of the Municipal non-profit Enterprise “Vinnytsia Central District Clinical Hospital” of Vinnytsia District Council, a SWOT analysis has been performed, which revealed the strengths and weaknesses of the medical institution, as well as opportunities and threats. Strengths are the focus on professionalism of staff, quality of management and medical services. Weaknesses are lack of funding, low autonomy in the ability to attract and dispose of funds, low staff remuneration. This, in turn, threatens staff turnover, reduces service delivery due to low solvency and high competition. Based on the results of the SWOT-analysis, the priorities of the institution’s development have been identified and strategic goals have been formulated. For example, improving the quality and expanding the list of medical services, increasing patient satisfaction, strengthening human resources, improving logistics of the medical institution, improving financial management. Specific measures have been developed to implement the goal of improving financial management. Additional sources of financing, formation of contractual relations with clear rules have been offered. The development strategy in 2021 will be largely determined by the further course of the pandemic and the dynamics of morbidity and the subsequent need to use the institution as an infectious disease hospital. All structural subdivisions of the institution are subject to constant development in order to be a leading, competitive, accessible hospital in the medical space and to provide a wide range of quality medical services aimed at improving the health of the population.
Keywords: anti-crisis financial management; strategic approach; SWOT-analysis; strategic goals